Priorities of German Oncologists. Results of the "choosing wisely" survey of the German Society of Hematology and Medical Oncology (DGHO) - Krause, Stefan; Oldenburg, Michael; Hallek, Michael; Neubauer, Andreas (Deutsche Medizinische Wochenschrift, 2017)
Background During the preparation of "choosing wisely" recommendations, the German Society of Hematology and Medical Oncology (DGHO) had performed a member survey. The large body of replies was systematically and quantitatively analyzed for this report. Methods Replies to the draft recommendations are quantified. Free text replies were iteratively categorized in three levels according to medical categories and additionally, according to their general target of necessary action. Results 492 members completed the survey within the given limit of 2 weeks. Draft recommendations against oversupply were widely supported (77 %-88 %). 1598 free text replies were analyzed. Unnecessary use of resources was requested in several fields in accordance with our recommendations. Strong demand was put forward regarding soft factors: "talking medicine", individually tailored therapy, supportive medicine and palliative care (51 % together) and social resources (11 %). Possible under-supply was less frequently described in fields of expensive measures (17 % of replies). Conclusion In the replies to our survey, we found a strong statement for a plus in talking medicine in oncology. Every physician caring for these patients can contribute to this demand. Structural improvements in continuing education and reimbursement in this field are desirable.
EVALuna2:25777